Bond-slip effect in novel steel box-concrete composite structures part Ⅰ: Short-term loading. (May 2023) - Chen, Hongbing; Zeng, Jiajin; Zhao, He; Liu, Xiaogang
Abstract: Steel box-concrete composite beam (SBCCB) is a novel type of steel–concrete composite structure. The concrete part at compressive zones is enclosed by the steel box without shearing studs at the interface between concrete and steel plates. Bond-slip effect on structural performance of SBCCBs needs to be quantitatively analyzed. In this study, the negative influence of bond-slip effect in SBCCB on stress redistribution and additional deflection is investigated. The differential equations of the bond-slip in SBCCB are established according to force equilibrium and compatibility deformation of micro unit and bond-slip strength of square concrete-filled steel tubular (CFST). To validate the feasibility of proposed theoretical equations, finite element models of SBCCB are constructed using spring elements to simulate the bond-slip mechanism between concrete and steel plates. Analytical solutions of deflection and stress agree well with numerical simulation results and experimental measurement. The research findings in this study can provide essential theoretical foundations for the structural design of practical SBCCB.